2016
DOI: 10.1186/s12913-016-1882-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of drug use patterns in terms of the WHO patient-care and facility indicators at four hospitals in Southern Ethiopia: a cross-sectional study

Abstract: BackgroundPatient-centered care is now the goal for virtually all healthcare systems. The aim of this research was to evaluate the patient care quality in regard to drug dispensing in four hospitals in southern Ethiopia namely Wolaita Sodo University teaching and referral hospital (WSUTRH), Tercha zonal hospital (TZH), Sodo Christian hospital (SCH) and Dubo St. Mary’s Catholic primary hospital (DSMCPH).MethodsA cross sectional study was conducted by using the WHO patient care and facility indicators between Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
32
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 11 publications
9
32
11
Order By: Relevance
“…The percentage of patient knowledge on this study was found to be 61.88%. This value is lower than other studies such as 70% in Zimbabwe [39] and 78.8% in southern Ethiopia [36]. The patient knowledge may fade further when the time goes on as expected from the quality of dispensing.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…The percentage of patient knowledge on this study was found to be 61.88%. This value is lower than other studies such as 70% in Zimbabwe [39] and 78.8% in southern Ethiopia [36]. The patient knowledge may fade further when the time goes on as expected from the quality of dispensing.…”
Section: Discussioncontrasting
confidence: 51%
“…The percentage of dispensed drugs was found similar with the average percent values of four hospitals in southern Ethiopia (86.3%). However, the percentage of labeled drugs in this study was much lower than the aforementioned setting (45.4%) [36]. The availability of essential drugs in the dispensary of healthcare settings is one indicator for quality of care.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…is finding was better than the study conducted in Ethiopia at selected health facilities where only one out of the four hospitals had a copy of the EDL, national drug formulary, and STG during the evaluation period, which makes the overall availability 25% [7]. e mean availability of essential key drugs was 64% in this study, which was comparable (65.7%) with a study conducted in four hospitals of South Ethiopia [25].…”
Section: Discussioncontrasting
confidence: 40%
“…These set of indicators could be used as benchmarks to enable the introduction of antibiotic stewardship programs (ASPs) in different healthcare settings [2,3,15]. Many studies have reported using the WHO indicators [17][18][19][20][21][22][23][24][25]. Studying prescribing patterns of medicines in general and antibiotic in particular aids in identifying irrational prescribing behaviors to make therapy more rational and cost effective [26].…”
Section: Introductionmentioning
confidence: 99%